Enhancing Curriculum and Student Experience through Project-Based Learning: Evidence from Underrepresented Minority and First-Generation Students in Information Systems Education - Sharma, Shwadhin; Gupta, Babita (Journal of University Teaching and Learning Practice, 2026)
The declining enrollment and retention of the students, including women and under-representative minorities (URM) in information systems and technology courses, have been increasingly challenging. This study assesses the efficacy of the project-based learning (PBL) instructional approach in the Information Systems (IS) major in increasing the retention of IS students. This longitudinal study uses a quantitative research methodology to evaluate the impact of PBL on control and experimental courses. The results find that PBL is an effective pedagogical approach and positively impacts a student’s satisfaction with the course, their career goals, test performance, perceived confidence, and overall recommendation of the course to other students. Results also imply that utilizing the PBL approach is effective in ensuring the same level of learning across different gender and first-generation students (first in the family to go to college). This study contributes to the scholarship on curriculum and assessment design by evaluating how a project-based learning (PBL) model can structure authentic, experiential assignments aligned with course learning objectives. Additionally, the study highlights how PBL can improve the student experience, particularly for underrepresented minority and first-generation students, through increased satisfaction and engagement.